STRUKTUR KOMUNITAS PARASITOID YANG BERASOSIASI DENGAN PENGOROK DAUN TANAMAN BAWANG MERAH DI BALI - Hamid (Jurnal Agrotech, 2019)
The existence of a type of parasitoid in an area with a certain height is largely determined by several factors, including the physical environment, space, feed sources, the presence of other parasites and human intervention. The purpose of this study was to determine the community structure of parasitoid associated with stone leek leafminer including abundance index, diversity index and dominance index in several locations of onion planting in Bali. Field surveys are conducted regularly during one planting season. On the location of onion plantations with an altitude of<500 m asl, covering the Badung Regency and Gianyar Regencies, on the onion planting area at that location no parasitoid was found (abundance index R1 = 0.00; diversity index H’= 0.00; dominance index D = 0.00). In locations with a height of ≥500-1000 m asl, covering several locations in Tabanan Regency, there were 2 types of parasitoid, Hemiptarsenus varicornis as many 3 adult (abundance index R1 = 0.6213; diversity index H’ = 0.2544; dominance index D = 0.0100) and Opius sp. 22 adult (abundance index R1 = 6.5239; diversity index H’= 0.1125; dominance index D = 0.7700). In locations with an altitude of ≥1000 m asl, covering several locations in Tabanan Regency and Bangli Regency, there were also 2 types of parasitoid namely H. varicornis 5 adult (abundance index R1 = 1.2941; diversity index H’ = 0.3380; dominance index D = 0.0433) and Opius sp. 17 adult (abundance index R1 = 5.1763; diversity index H’= 0.2013; dominance index D = 0.5887).